Method Implementation Active Learning in the Learning of Islamic Religion Education - Susanti, Weti; Jannah, Miftahul; Khoiriyah, Latifah (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2020)
This article will discuss how a teacher can create a conducive and pleasant classroom atmosphere by applying the active learning method for the creation of students who can think critically, and creatively and apply it in learning. The purpose of this article is to explain the implications of active learning methods to create a conducive and comfortable learning atmosphere for the creation of students who can think critically and creatively and apply them in learning. In general, the conclusion of this article finds that to carry out the learning process using the active learning method, it is necessary to go through twelve steps with five steps carried out by the teacher, namely, first, the teacher explains learning indicators, the second teacher checks student learning readiness, the third teacher motivates students, the fourth teacher Knowing the problems that exist in students, the five teachers actively scrape the answers to students' questions. There are seven steps of implementation carried out by students consisting of first, students discuss the material given by the teacher in the learning process, second, students read and look for relevant sources while the discussion is ongoing, third students think about solving problems about the material being studied, fourth students determine alternative problem solving from the material being studied, five students determine other alternatives in solving the problems being studied, six students can present the results of the ongoing discussions in class, seven students actively explain answers to other students' questions during the discussion.